C6 glioma neuronal interactions and their moderation by the tryptophan-kynurenine metabolism pathway - Rakovets, Yuliia (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2021)
Brain glia possess the rate limiting enzyme indoleamine 2, 3-dioxygenase (IDO) which catalyses the conversion of tryptophan to kynurenine. Microglia also express kynurenine monooxygenase (KMO) and kynureninase (KYNU) which lead to the production of the excitotoxin quinolinic acid and other free radical producing metabolites. Conversely astrocytic glia express kynurenine aminotransferase (KAT) which leads to the production of kynurenic acid (KYNA), which acts as an NMDA receptor antagonist and is reported to have neuroprotective properties. Previous investigations have confirmed that IFNγ-stimulated kynurenine pathway (KP) induction in microglia reduces neurite outgrowth and complexity, and that these alterations may be abrogated using pharmacological inhibitors of the KP. In this investigation these findings were extended by assessing a role for the KP in mediating changes associated with C6 glioma cells, a rat glioma cell line. Conditioned media (CM) from C6 cells was placed on mature primary cortical neurons for 24h. Neurons were fixed, and neurite outgrowth and complexity were assessed using fluorescent immunocytochemistry followed by Sholl analysis. Furthermore, the co-localised expression of synaptic proteins synaptophysin and the post synaptic density 95 (PSD-95) were determined. Results show increased mRNA expression of IDO in C6 cells compared to rat primary mixed glial cells. Conditioned media from C6 cells reduced neurite outgrowth and complexity and co-localised expression of synaptic markers with reductions in these parameters prevented when C6 cells were pre-treated with the IDO inhibitor, 1-methyltryptophan (1-MT) (L) (0.5mM) or when KYNA (0.3 µM) was co-applied directly to neurons. Furthermore, conditioned media from C6 glioma cells had no effect on neuronal viability yet altered microglial and astroglial morphology towards an activated state as observed by ionized calcium-binding adapter molecule 1 and glial fibrillary acidic protein immunoreactivity respectively; effects which were also partially rescued by prior treatment of C6 cells with 1-MT. Overall, this study indicates that inhibition of the KP in C6 cells may be targeted to protect against C6 glioma cell associated neuronal atrophy. Alternatively activating the neuroprotective branch of the KP by raising KYNA concentration may also provide protection from glioma-associated neuronal atrophy.
APPROVED
Keywords: Kynurenine pathway; Glioma; Glia; Primary Cortical Neurons